#### Answer

$\frac{3}{2}$

#### Work Step by Step

$\frac{2\pi r^2+2\pi r(2r)}{4\pi r^2}$=$\frac{6\pi r^2}{4\pi r^2}$=$\frac{6}{4}$=$\frac{3}{2}$

Chegg costs money, GradeSaver solutions are free!

Published by
Brooks Cole

ISBN 10:
9781285195698

ISBN 13:
978-1-28519-569-8

$\frac{3}{2}$

$\frac{2\pi r^2+2\pi r(2r)}{4\pi r^2}$=$\frac{6\pi r^2}{4\pi r^2}$=$\frac{6}{4}$=$\frac{3}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.